2015
DOI: 10.1155/2015/726012
|View full text |Cite|
|
Sign up to set email alerts
|

β-Catenin-Dependent Signaling Pathway Contributes to Renal Fibrosis in Hypertensive Rats

Abstract: The mechanism of hypertension-induced renal fibrosis is not well understood, although it is established that high levels of angiotensin II contribute to the effect. Since β-catenin signal transduction participates in fibrotic processes, we evaluated the contribution of β-catenin-dependent signaling pathway in hypertension-induced renal fibrosis. Two-kidney one-clip (2K1C) hypertensive rats were treated with lisinopril (10 mg/kg/day for four weeks) or with pyrvinium pamoate (Wnt signaling inhibitor, single dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
3
13
0
Order By: Relevance
“…Masson's staining showed that the renal fibrosis was significantly elevated in 2K1C rats compared with Sham rats, which was consistent with previous findings ( 33 35 ). Intraperitoneally administrated with high dose of vaccarin or captopril abrogated the fibrosis in the right kidney in 2K1C rats ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Masson's staining showed that the renal fibrosis was significantly elevated in 2K1C rats compared with Sham rats, which was consistent with previous findings ( 33 35 ). Intraperitoneally administrated with high dose of vaccarin or captopril abrogated the fibrosis in the right kidney in 2K1C rats ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…In addition, in the mouse collecting duct cell line M1, ANG II induces ␤-catenin protein, fibronectin mRNA, and collagen I mRNA, which are attenuated with ␤-catenin destabilization reagent pyrvinium pamoate (192). Moreover, pyrvinium pamoate treatment ameliorates kidney induction of ␤-catenin, collagen I, fibronectin, and osteopontin in a rat model of renovascular hypertension, suggesting the role of the Wnt/␤-catenin pathway in ANG II-dependent renal fibrosis (193). It is also interesting to note that multiple RAS genes are targets of the Wnt/␤-catenin pathway.…”
Section: Wnt/␤-catenin Pathwaymentioning
confidence: 94%
“…AngII enhances Wnt1 expression, β-catenin nuclear translocation in mouse podocytes, with inhibition of Wnt/β-catenin pathway attenuating podocyte injury (139). β-catenin destabilization reagent also inhibits AngII-induced β-catenin, collagen I, fibronectin and osteopontin in mouse collecting duct cell or kidney of renovascular hypertensive rat (140, 141). Thus, there is accumulating evidence indicating a close relationship between the Wnt/β-catenin pathway and AT1 receptor in regard to cardiovascular remodeling and chronic kidney diseases.…”
Section: Cascades Of Wnt Notch Hippo and Mitochondriamentioning
confidence: 99%